PEMBENTUKAN DAN PEMBEKALAN DOKTER CILIK SEBAGAI UPAYA PEMBERDAYAAN ANAK SEKOLAH DASAR SEBAGAI PROMOTOR KESEHATAN GIGI & MULUT DI LINGKUNGAN SEKOLAHNYA - nuryati, sri; Habibah, siti sabatul; Danan, Danan (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Dental caries is one of the most common chronic and endemic diseases in school-aged children. Untreated caries can affect weight, growth, quality of life and impact the health of permanent teeth. External factors that influence the occurrence of dental caries are the level of knowledge, attitudes and behavior of children in oral health. By empowering children's independent ability to obtain their oral health status, it is hoped that the Caries Free Program can be realized. The expected form of independence is that school children are able to gain knowledge, attitudes and positive behaviors independently. This can be realized if there is an active change of agent in their peer environment. The formation of the Little Doctor Team in this school environment is expected to make them a Promoter of Dental & Oral Health in their peer environment. The purpose of the Community Service is to form a Little Doctor Team in Elementary School, equip them with knowledge about how to brush their teeth properly, as well as the introduction of Basic Dental & Oral Health Tools at SD Islam Al Madani Banjarbaru. The target of Community Service is selected students of SD Islam Al Madani Banjarbaru who are formed into a Little Doctor Team. The problem can be solved by forming a Little Doctor Team, as well as providing briefings on how to brush teeth properly and simple Dentistry Tools.